Assessment of persistent organic pollutants and their relationship with immunoglobulins in blood of penguin colonies from Antarctica - Cardenas, Claudia; Jara, Solange; Celis, José E.; Araneda, Alberto; González, Margarita; Espejo, Winfred; Barra, Ricardo (Austral Journal of Veterinary Sciences, 2018)
Persistent organic pollutants (POPs) may affect the immune system of seabirds, and some field studies have examined this effect. There are evidences that POPs cause negative effects on the immune system, but in Antarctic penguins data are scarce. In order to assess the risks that POPs may have on wild animals, some immunological studies constitute a good alternative. Determining the levels of immunoglobulins can deliver relevant information about the potential impact of POPs in seabirds from different environments. However, there are very few records in penguins so far. The aim of the present work was to quantify the concentrations of polychlorinated biphenyls (PCBs), hexachlorobenzene (HCB), dichlorodiphenyltrichloroethane (ΣDDT), endosulfans, and immunoglobulin IgY in blood samples of colonies of chinstrap penguins (Pygoscelis antarctica) that inhabit in the Antarctic Peninsula area. Analysis of POPs in blood samples was carried out through extraction with QuEChERS method, followed by gas chromatography. Detection of IgY concentrations was achieved by ELISA test, using anti-chicken antibodies. There was some significant correlation between immunoglobulin and the presence of PCBs and endosulfans. Even though the levels of these pollutants are low to cause any biological effect on the birds, the results are indicating some influence on the IgY concentrations in penguin blood.